Extraction of Nuclear and Non-ferrous Metals - Dutta, Sujay Kumar (Topics in Mining, Metallurgy and Materials Engineering,, 2018)
This book presents a comprehensive overview of non-ferrous metallurgy, especially its core principles and fundamental aspects, in a concise form. The book covers all basic concepts and definitions related to metal extraction, and provide succinct summaries of relevant metallurgical processes. It also covers the scientific and engineering aspects of nuclear processes and features special chapter on ultra-high-purity metals. The book employs a step-by-step approach, is written in an easy-to-understand style, and discusses significance of core concepts. As such, it not only offers a valuable guide for professionals and researchers working in the areas of metallurgy, mining, and chemical engineering, but can also be used as a core text in both graduate and professional coursework.